Osoba trzecia w toku egzekucji administracyjnej z rzeczy ruchomej i nieruchomości podatnika - Ostojski, Przemysław (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article concerns the issue of the situation of a third party in the course of enforcement proceedings to movable and immovable property of a taxpayer. The analysis carried out in the study concerns the legal basis of interfering into the assets of the third party in the course of enforcement of tax arrears.The results of the study reveal that pending the course of the enforcement proceedings the legislator determined the realization of the material tax law from the benefit of the party which is the usage of the right to exclude the assets from execution. Otherwise the interference in the assets of a third party is permissible, even though that person is not the subject of enforceable obligation, nor is it subject to liability in respect of tax liability.
Keywords: osoba trzecia w egzekucji administracyjnej; egzekucja administracyjna zobowiązań pieniężnych; egzekucjaz ruchomości; egzekucja z majątku nieruchomego; egzekucja z udziału we własności nieruchomości